Short-Term Outcomes of Synovectomy and Total Knee Replacement in Patients with Diffuse-Type Pigmented Villonodular Synovitis - Su, Weiping; Zhou, Yangying; Lu, Wei; Zeng, Min; Hu, Yihe; Xie, Jie (The Journal of Knee Surgery, 2019)
Diffuse-type pigmented villonodular synovitis is a rare benign disease that causes disorders of the knee, including erosion of subchondral bone and cyst formation, with eventual osteoarthritis. The purpose of this study was to evaluate the short-term outcomes of synovectomy and total knee replacement in patients with the diffuse type of pigmented villonodular synovitis. From November 2011 to May 2015, we performed synovectomy and total knee replacement in 28 patients with diffuse pigmented villonodular synovitis diagnosed on the basis of histopathology of biopsy specimens. Clinical data were collected perioperatively and during follow-up for evaluation of surgical efficacy. No intraoperative complications were encountered. Mean operative duration was 73.4 minutes (range: 47–115 minutes); mean estimated blood loss was 223.9 mL (range: 50–600 mL). The mean duration of follow-up was 58.7 months (range: 36–84 months). Mean range of motion improved from 86.1 ± 11.3 degrees (range: 60–100 degrees) to 107 ± 11.4 degrees (range: 90–130 degrees). Average Knee Society clinical scores improved from 38.9 ± 9.5 (range: 17–54) to 84.4 ± 6.1 (range: 75–98); functional scores improved from 48.9 ± 13.1 (range: 25–80) to 84.6 ± 6.1 (range: 75–95; p < 0.05 for both). Postoperative radiographs showed no signs of prosthesis loosening, periprosthetic fractures, or dislocation. The short-term efficacy of synovectomy and total knee replacement in treating patients with diffuse pigmented villonodular synovitis was satisfactory.
Keywords: Diffuse pigmented villonodular synovitis; total knee replacement; tenosynovial giant cell tumor; total synovectomy